A Study on the Effects of Biodiversity and Conservation Efforts on Community Health in the Sunderban Area of Eastern India - Goswami, Haimanti; Debnath, Sagar; Mukherjee, Soumen; Biswas, Swarnava (International Journal of Statistics in Medical Research, 2024)
The Sunderbans, located at the southernmost tip of the Bay of Bengal, is a UNESCO World Heritage site renowned for its mangrove extent encompassing tidal rivers, mudflats, and islands. As the home of the Royal Bengal Tiger and countless humans, it represents the ecological centre of Eastern India. The primary objective of this study is to analyse community participation in Sunderbans conservation strategies. We are in a position to identify the primary catalysts and inhibitors of such community engagement by understanding the correlation between active conservation participation and health outcomes. The essence of the study emphasises the community's awareness of environmental factors that affect the health. Our ultimate objective is to design a framework that clarifies the connections between conservation and health initiatives in areas of high biodiversity. Using a mixed-methods approach, quantitative biodiversity metrics were derived using species richness, evenness, and Simpson's Diversity Index, and health data were gathered using standardised community health surveys that focused on disease prevalence, nutrition status, and sanitation practises. Twenty sites with differing degrees of community-based conservation activities provided the data. Using sophisticated statistical methods, such as multivariate regression analyses and non-metric multidimensional scaling, patterns and correlations between biodiversity and health indicators were identified. Preliminary results indicated a correlation between biodiversity metrics and specific health indicators. There was a 16.8% decrease in waterborne maladies and a 12.1% increase in nutritional diversity among community members in areas with greater biodiversity. Additionally, areas with robust community-based conservation activities demonstrated a 19.8% increase in biodiversity and community health metrics in comparison to areas with minimal to no conservation activities. Our findings highlight the necessity of merging conservation and health agendas, arguing for an integrative strategy in biodiverse regions. It is in the best interest of global stakeholders to recognise and exploit such potential in comparable ecologies.